KEWENANGAN NOTARIS TERHADAP PENDIRIAN PERSEROAN TERBATAS PERORANGAN BERDASAR UUJN DAN PP NOMOR 8 TAHUN 2021 - Muhammad Boma Adichandra (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research is entitled "Notary Authority for the Establishment of Individual Limited Liability Companies Based on the Law and Government Regulation Number 8 of 2021", the first issue to be studied; regarding what is the authority of the Notary in the establishment of an Individual Limited Liability Company based on the Law and Government Regulation Number 8 of 2021, and second; regarding the concept of an individual PT whether it is in accordance with the concept of an agreement of a PT in Law 40 of 2007. This type of research is normative legal research supported by the information of the source. The researcher uses a legislative and conceptual approach. Legal materials use Primary and Secondary Legal Materials collected by means of literature studies and interviews with resource persons. From the legal materials that have been collected, they are analyzed qualitatively. The results of the study show that, firstly; Notaries do not have the authority to make a deed of establishment of an Individual Limited Liability Company, because the establishment process of an Individual PT can be carried out by its founder only by making a statement of establishment in Indonesia on the Ministry of Law and Human Rights Website. Second, the concept of an Individual PT is not in accordance with the concept of a limited liability company agreement based on Law Number 40 of 2007 concerning Limited Liability Companies. The researcher gave suggestions, namely first; there needs to be a regulation related to the role of Notaries in the establishment of Individual Universities to assist founders in the establishment of Individual Companies, and secondly; The need for socialization from the government to third parties, namely banking, regarding the legal entity of PT Perorang in providing capital to small and micro businesses, not only to the founder of PT Perorangan.